Sentencing and mental disorder: the evolution of the Verdins Principles, strategic interdisciplinary advocacy and evidence-based reform. Issue 5 (3rd September 2022) - Walvisch, Jamie; Carroll, Andrew; Marsh, Tim
Abstract : In DPP v O'Neill, the Victorian Court of Appeal excluded personality disorders from the scope of the sentencing principles that apply to offenders with mental health problems around Australia (the ' Verdins principles'). This decision was based on a fundamental misunderstanding of the nature of personality disorders and had the potential to create serious injustice for many marginalised people. To redress this problem, the authors engaged in a unique process of strategic advocacy, which resulted in the Victorian Court of Appeal overturning O'Neill in the recent case of Brown v The Queen . This article examines the evolution of the Verdins principles, the problems that arose in O'Neill, the collaborative strategy used to address those problems and the successful outcome of that interdisciplinary strategy.